(untitled) (Journal of Economic Research & Business Administration, 2016)
In the current economic conditions of the infrastructure and the design departments of transport and logistics infrastructure of the country is important. In terms of innovation development of economy, transport is seen as a major factor of social and economic growth of the state. The transport system of the country provides: – unity of the economic space of the country; – improvement of inter-regional and international transport and economic links; – rationalizing the distribution of productive forces; – more efficient use of natural resources; – business development and the development and expansion of international cooperation. Accelerated development of the processes of globalization on the world of transport and logistics market, logistics companies require the country’s widespread use in the work of advanced technology and innovative schemes to enhance the company’s competitiveness and further development of logistics infrastructure.